In vitro evaluation of antifungal potential of imidazolium salts against Candida albicans - Thomas Fernando Mallmann; Guilherme Stein Porto Alegre; Vinícius Demétrio da Silva; Henri Stephan Schrekker; Lina Naomi Hashizume (Universidade Federal do Rio Grande do Sul. Faculdade de Odontologia, 2021)
Aim: This study aims to evaluate the antifungal potential of imidazolium salts (IS) against Candida albicans. Material and methods: Antifungal evaluation of the IS was performed using the disk diffusion test, using a strain of Candida albicans (ATCC 90028). Five different IS were synthesized and tested in the present study: 1,8-bis(methylimidazolium-1-yl) octane bromide (MImC8MImBr2), 1,12-bis(methylimidazolium-1-yl) dodecane methanesulfonate (MImC12MIm(MeS)2), 1-n-hexadecyl-2,3-dimethylimidazolium chloride (C16DMImCl), 1,10-bis(methylimidazolium-1-yl) decane methanesulfonate (MImC10MIm(MeS)2) e 1,10-bis(methylimidazolium-1-yl) decane bromide (MImC10MImBr2). Cetylpyridinium chloride (C16PyrCl) was used as a reference substance. Chlorhexidine (C34H54Cl2N10O14) and saline (NaCl 0,9%) solutions were positive and negative controls, respectively. Results: Among the tested IS, MImC12MIm(MeS)2, MImC10MIm(MeS)2 and MImC10MImBr2 showed the following values for inhibition halos: 28,00 mm, 20,50 mm and 18,75 mm, respectively. These values were similar or superior than those found for the positive control (14.87 mm) and reference (0 mm) substances. Discussion: IS can be a promising alternative to antifungal conventional therapies, as exemplified in previous studies. However, further in vitro and in vivo studies are needed to assess the antifungal potential of these compounds against Candida-mixed biofilms. Conclusion: Based on these results, there are three in vitro promising antifungal potential against Candida albicans IS tested in this study.